SOCIAL MEDIA TOOLS: FOSTERING COLLABORATION, KNOWLEDGE TRANSFER AND INNOVATION WITHIN COOPERATIVES (Third Sector Social Economic Review, 2017)
The present study analyses how an enterprise micro-blogging tool is used to promote knowledge transfer, collaboration and innovation within the context of a cooperative in Mexico.Through an inductive qualitative research based on semi-structured interviews with users, promoters and non-users, the paper identifies a number of benefits derived from the use of the micro-blog that impact upon the collaboration within members of cooperatives, the organisational environment, the knowledge management’s practices, and the innovation processes of the cooperative. The study is limited to considering the use and benefits of a corporate micro-blog in the context of a cooperative organisation in Mexico; however, it includes implications that can help make decisions to those seeking to implement social media tools in their organisations in order to foster collaboration, innovation and knowledge transfer.
Keywords: Micro-blogging; Social Media; Adoption and Usage; Cooperatives; Mexico City